Uczestnictwo filii zagranicznych w rozwoju zasobu wiedzy korporacji transnarodowych - Zorska, Anna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2014)
The article aims to portray important changes in the activity of TNCs’ foreign subsidiaries which result in the increased participation of subsidiaries in develop‑ ment of knowledge resource and competitiveness by parent firms. Knowledge flows evolve under growth of activity and changed functioning of foreign subsidiaries and recently various factors have contributed to expanding process coined a cre‑ ative transition of TNCs’ foreign subsidiaries. The process consists in increased engagement of foreign subsidiaries in conducting own R&D and creating a new knowledge as well as acquiring knowledge form various external sources, mostly from local entities in host countries. Competitiveness of subsidiaries is sustained and a reverse technology transfer to parent firm is initiated. “Local embedded‑ ness” of TNCs’ subsidiaries offers more possibilities to tap to knowledge itself and knowledge ‑creating local resources and capabilities, first of all by means of participation in regional and national innovations systems (or networks). It can result in draining local market of knowledge and other resources/capabilities, next in leaking new knowledge out of the country, and finally in inhibiting innovation and competitiveness of firms and economy of the host country.